1986
DOI: 10.1152/jappl.1986.61.1.312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breathing dry air on structure and function of airways

Abstract: We compared the effect of breathing dry air (0.70 mg H2O/l) with that of breathing room air (8.62 mg H2O/l) in guinea pigs anesthetized with urethane. The data showed that breathing dry air caused a reduction of extravascular water (EVW) in the trachea (P less than 0.01) but not the lung. Structural analysis showed that this water loss occurred from the loose connective tissue of the submucosa. Histamine dose response curves performed on the animals showed that breathing dry air caused an increase in the maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 0 publications
0
17
0
3
Order By: Relevance
“…That substantial proximal airway water loss can occur under these circumstances seems certain. Van Oostdam et al (34) and Barbet and colleagues (35) both showed evidence for severe airway dehydration in guinea pigs subjected to dry gas breathing through a tracheostomy. Direct measurements of airstream water vapor fluctuations within the central airways of mechanically hyperventilated dogs (36) also demonstrate that dry gas hyperpnea imposes substantial water losses within the central airways.…”
Section: Discussionmentioning
confidence: 99%
“…That substantial proximal airway water loss can occur under these circumstances seems certain. Van Oostdam et al (34) and Barbet and colleagues (35) both showed evidence for severe airway dehydration in guinea pigs subjected to dry gas breathing through a tracheostomy. Direct measurements of airstream water vapor fluctuations within the central airways of mechanically hyperventilated dogs (36) also demonstrate that dry gas hyperpnea imposes substantial water losses within the central airways.…”
Section: Discussionmentioning
confidence: 99%
“…19 Airway resistance increases to protect the lungs from the challenge of dry and cold gas by reducing the air flow in the upper airways and trachea. 3,4 Breathing dry air causes excessive water loss by the nasal mucosa, 20 which may in turn reduce the nasal mucoclliary clearance rate via changes in the rheological properties or adhesiveness of nasal mucus and/or slowing of ciliary pulses. 5 Unwarmed and dry gas may have adverse effects on patients with respiratory failure.…”
Section: Adverse Effects Of Lack Of Humidificationmentioning
confidence: 99%
“…The volume, flow, and pressure signals were recorded using a General Scanning recorder (model RS4-5P). Pulmonary resistance (RL) was calculated from these signals with the method of von Neergaard and Wirz [17], using a computerized system developed in this laboratory [18]. RL was measured at baseline after 5 breaths of aerosolized Tyrode's solution and after increasing breaths (3 mL each) of an aerosolized solution (2 mg/mL) of histamine (1, 2, 3, 4, 5, 8, 10, 20, 30, 40, 50, 60 breaths) until 60 breaths were delivered or until a plateau of response was observed, Aerosols were generated from an Acorn nebulizer driven by air at 3.8 L/min.…”
Section: Bronchial Responsivenessmentioning
confidence: 99%